2015
DOI: 10.1371/journal.pone.0142400
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of GATA2 in the Negative Regulation of Type 2 Deiodinase Gene by Liganded Thyroid Hormone Receptor β2 in Thyrotroph

Abstract: The inhibition of thyrotropin (thyroid stimulating hormone; TSH) by thyroid hormone (T3) and its receptor (TR) is the central mechanism of the hypothalamus-pituitary-thyroid axis. Two transcription factors, GATA2 and Pit-1, determine thyrotroph differentiation and maintain the expression of the β subunit of TSH (TSHβ). We previously reported that T3-dependent repression of the TSHβ gene is mediated by GATA2 but not by the reported negative T3-responsive element (nTRE). In thyrotrophs, T3 also represses mRNA of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 67 publications
(151 reference statements)
3
14
0
Order By: Relevance
“…Interestingly, however, the D2 gene harbors the two highly conserved GATA-REs [47]. As expected, our previous work revealed that liganded TRβ2 suppresses the D2 promoter by a tethering mechanism via GATA2 on these GATA-REs [47]. In the GATA2 gene, the critical function of +9.5 kb GATA-RE ( Fig 1A) was evidenced based on hematopoietic stem/progenitor cell depletion observed in the mice harboring the deletion of this GATA-RE [45].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Interestingly, however, the D2 gene harbors the two highly conserved GATA-REs [47]. As expected, our previous work revealed that liganded TRβ2 suppresses the D2 promoter by a tethering mechanism via GATA2 on these GATA-REs [47]. In the GATA2 gene, the critical function of +9.5 kb GATA-RE ( Fig 1A) was evidenced based on hematopoietic stem/progenitor cell depletion observed in the mice harboring the deletion of this GATA-RE [45].…”
Section: Discussionsupporting
confidence: 66%
“…Although T3 has been known to repress type-2 deiodinase (D2) gene/activity in several organs and cultured cells including thyrotroph [67], no DNA sequence similar to the nTRE reported in the TSHβ gene has been identified in this gene to date [68,69]. Interestingly, however, the D2 gene harbors the two highly conserved GATA-REs [47]. As expected, our previous work revealed that liganded TRβ2 suppresses the D2 promoter by a tethering mechanism via GATA2 on these GATA-REs [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that THs induce their repression instead of their activation. This is the case of genes of the TH pathway such as the thyrotropin-releasing hormone (TRH) gene or the deiodinase 2 [49,50]. If Pm542 and Pm8742 are somehow specialized in the negative TREs, they may account for the drop of global TH levels observed in lamprey metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that the negative regulation of human TSHB gene exerted by T 3 is independent of nTRE (Matsushita et al 2007, Matsunaga et al 2015.…”
Section: Negative Transcriptional Regulation Of Cga and Tshb Genes Bymentioning
confidence: 99%